2006
DOI: 10.1158/0008-5472.can-06-0900
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/Paracrine Platelet-Derived Growth Factor Regulates Proliferation of Neural Progenitor Cells

Abstract: Growth factors play an important role in regulating neural stem cell proliferation and differentiation. This study shows that platelet-derived growth factor (PDGF) induces a partial differentiation of neural stem/progenitor cells (NSPCs) in the absence of other mitogens in vitro. NSPCs thus acquire an immature morphology and display markers for both neurons and glia. In addition, these cells do not readily mature in the absence of further stimuli. When NSPC cultures treated with PDGF were exposed to additional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…Signaling through this receptor is critical for important events that dictate the fate of gonocytes, the precursors of the SSC, including resumption of proliferation, inhibition of apoptosis, and migration. Analogously to what was reported in neurons (52), PDGFR activation could act as a mitogen in the early phase of stem cell differentiation to expand the pool of immature gonocytes. Furthermore, PDGFR-␤ could stimulate the differentiation of gonocytes toward SSC.…”
Section: Discussionsupporting
confidence: 56%
“…Signaling through this receptor is critical for important events that dictate the fate of gonocytes, the precursors of the SSC, including resumption of proliferation, inhibition of apoptosis, and migration. Analogously to what was reported in neurons (52), PDGFR activation could act as a mitogen in the early phase of stem cell differentiation to expand the pool of immature gonocytes. Furthermore, PDGFR-␤ could stimulate the differentiation of gonocytes toward SSC.…”
Section: Discussionsupporting
confidence: 56%
“…Next we investigated whether estrogens would modulate the effect of PDGF, a mitogen for oligodendrocyte precursor cells (3). We found that the number of NG2-positive cell was 42 ± 3.0% in the presence of PDGF (Fig.…”
Section: Effect Of E2 or Bpa On Differentiation Of Nscsmentioning
confidence: 96%
“…Recent in vitro studies on the effects of PDGF signaling on neural stem/progenitor cell differentiation also demonstrate a growth-promoting effect on progenitor cells and an inhibition of differentiation [Erlandsson et al, 2006]. Exposure to PDGF in the first half of the differentiation paradigm resulted in a delay in both neuron and oligodendrocyte differentiation.…”
Section: Pdgfr ␣ -Expressing Astrocytes In the Svz Are Primary Progenmentioning
confidence: 99%